Development of New Models for the Estimation of Hourly Components of Solar Radiation: Tests, Comparisons, and Application for the Generation of a Solar Database in Morocco - Mohammed Benchrifa; Rachid Tadili; Ahmed Idrissi; Hajar Essalhi; Abdellah Mechaqrane (International Journal of Photoenergy)
All studies of solar systems need the hourly values of solar fluxes related to the different components of solar radiation. However, for most sites, measurements are not available. The goal of this paper is to establish an hourly solar radiation data bank for the entirety of Morocco. This data bank will contain the energetic components (global, diffuse, direct, and inclined solar radiation) and the spectral components (ultraviolet IUV, infrared IIR, and photosynthetically active radiation IPAR). To create this database, in the beginning, we build up models for predicting the various components of the hourly solar radiation, from measurements provided by the different stations owned by the Laboratory of Solar Energy and Environment (LESE). Then, these equations will be verified by using statistical tests. Moreover, we compared our results with those obtained by similar studies. Finally, based on the daily database of global radiation provided by the Laboratory of Solar Energy and Environment, we created an hourly database that unites the various components of solar radiation over 10 years for the entirety of Morocco. Regarding the validity study, the statistical indicators showed that the used models have minimal errors that do not exceed, for the global radiation, -2.93% in Rabat, -3.9% in Tangier,-3.28% in Marrakech, and -0.85% in Fez, and for diffuse radiation, -1.09% in Rabat, -0.68% in Fez,-3.08% in Tangier, and -2.49% in Marrakech. These results show the good quality of the used estimation models. Thus, the data bank that we have realized will fill the gap of the hourly solar data and will meet the needs of engineers, installers of solar systems, and researchers who often need an extensive database.